3-Iodothyronamine, a Novel Endogenous Modulator of Transient Receptor Potential Melastatin 8? - Khajavi, Noushafarin; Mergler, Stefan; Biebermann, Heike (Frontiers in Endocrinology, 2017)
The decarboxylated and deiodinated thyroid hormone derivative, 3-iodothyronamine (3-T1AM) is suggested to be involved in energy metabolism and thermoregulation. G protein-coupled receptors (GPCRs) are known as the main targets for 3-T1AM; however, transient receptor potential channels (TRPs) were also recently identified as new targets of 3-T1AM. This article reviews the current knowledge of a putative novel role of 3-T1AM in the modulation of TRPs. Specifically, the TRP melastatin 8 (TRPM8) was identified as a target of 3-T1AM in different cell types including neoplastic cells, whereby 3-T1AM significantly increased cytosolic Ca2+ through TRPM8 activation. Similarly, the β-adrenergic receptor is involved in 3-T1AM-induced Ca2+ influx. Therefore, it has been suggested that 3-T1AM-induced Ca2+ mobilization might be due to β-adrenergic receptor/TRPM8 channel interaction, which add to the complexity of GPCR regulation by TRPs. It has been revealed that TRPM8 activation leads to a decline in TRPV1 activity, which may be of therapeutic benefit in clinical circumstances such as treatment of TRPV1-mediated inflammatory hyperalgesia, colitis, and dry eye syndrome. This review also summarizes the inverse association between changes in TRPM8 and TRPV1 activity after 3-T1AM stimulation. This finding prompted further detailed investigations of the interplay between 3-T1AM and the GPCR/TRPM8 axis, and indicated the probability of additional GPCR/TRP constellations that are modulated by this thyroid hormone derivative.